Regional Variation in New Firm Formation in Turkey: Cross-Section and Panel Data Evidence - Miyase Yesim Köksal (European Regional Science Association (ERSA), 2003)
Since the 1980s the promotion of the formation of new firms has been considered as the main policy in dealing with the problem of uneven regional economic development in many countries. The determination of regional characteristics that are influential on new firm formation is quite a bit essential to develop realistic and efficient policies to solve this problem. Turkey is one of the countries with a substantial variation in new firm formation across her regions which are also significantly diversified in terms of social and economic structures. In this context, the present study explores the variation in new firm formation in manufacturing sector across regions of Turkey and investigates the effects of regional characteristics on new firm formation. Furthermore, the study provides a comparison of the differences in regional variation in underlying firm birth processes between developed countries and Turkey as a representative of a developing country. The results of the cross-section and panel data analyses show that population density is the most significant variable in explaining regional variation in new firm formation in manufacturing sector in Turkey. Such an outcome supports the urban incubator theory implying that urban context contributes to new firm formation in manufacturing in Turkey. Keywords: New Firm Formation, Regional Characteristics
Keywords: 330